Antiproliferative Activity of Ethanolic Extract of Ciplukan Herbs (Physalis angulata L.) on 7,12-Dimethylbenz[a]nthracene-Induced Rat Mammary Carcinogenesis - Monikawati, Ameilinda; Farida, Sofa; Putri, Laras Widawaty; Ikhtiarsyah, Yurista Gilang; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2011)
Physalis angulataÃÂ  L.ÃÂ  isÃÂ  anÃÂ  annualÃÂ  herbÃÂ  widelyÃÂ  usedÃÂ  asÃÂ  popularÃÂ  medicineÃÂ  forÃÂ  the treatment of cancer. Physalis angulata L. ethanolic extract (PEE) has been demonstrated to have strong cytotoxic activity against breast cancer, inhibited cancer cellÃ¢â¬â¢s proliferation and inducedÃÂ  cellÃÂ  cycleÃÂ  arrest.ÃÂ  TheÃÂ  aimÃÂ  ofÃÂ  ourÃÂ  studyÃÂ  isÃÂ  toÃÂ  investigateÃÂ  theÃÂ  effectÃÂ  ofÃÂ  PEEÃÂ  asÃÂ  a cancerÃÂ  chemopreventiveÃÂ  agentÃÂ  onÃÂ  7,12-dimethylbenz[a]nthraceneÃÂ  (DMBA)-inducedÃÂ  rats mammary. The antiproliferative activity was characterized by monitoring the histopatology representationÃÂ  andÃÂ  expressionÃÂ  ofÃÂ  cellÃÂ  proliferationÃÂ  onÃÂ  DMBA-inducedÃÂ  mammaryÃÂ  ratsÃÂ  that wereÃÂ  treatedÃÂ  withÃÂ  PEEÃÂ  againstÃÂ  controlÃÂ  groups.ÃÂ  TheÃÂ  histopatologyÃÂ  representationÃÂ  were analyzedÃÂ  byÃÂ  HaematoksilinÃÂ  EosinÃÂ  (HE)ÃÂ  stainingÃÂ  method,ÃÂ  whileÃÂ  proliferativeÃÂ  activityÃÂ  was detected by AgNOR method. The HE staining results showed significant differences in cells morphologyÃÂ  ofÃÂ  treatmentÃÂ  groupsÃÂ  comparedÃÂ  toÃÂ  theÃÂ  controlÃÂ  groups.ÃÂ  ThusÃÂ  resultsÃÂ  suggest thatÃÂ  PEEÃÂ  wasÃÂ  ableÃÂ  toÃÂ  repairÃÂ  morphologyÃÂ  ofÃÂ  cellsÃÂ  undergoingÃÂ  carcinogenesis.ÃÂ  AgNOR methodÃÂ  showedÃÂ  decreasingÃÂ  occurrenceÃÂ  ofÃÂ  blackÃÂ  dotsÃÂ  betweenÃÂ  treatmentÃÂ  andÃÂ  control groups. Thus, we conclude that PEE has an antiproliferative activity on DMBA-induced rat mammary.ÃÂ  Therefore,ÃÂ  theÃÂ  ethanolicÃÂ  extractÃÂ  ofÃÂ  PhysalisÃÂ  angulataÃÂ  herbsÃÂ  isÃÂ  aÃÂ  potential chemopreventive agent on cancer. Further study on its molecular mechanism needs to be explored. Keywords:ÃÂ  PhysalisÃÂ  angulata,ÃÂ  breastÃÂ  cancer, 7,12-dimethylbenz[a]nthracene, carcinogenesis, antiproliferative